2009
DOI: 10.1097/pap.0b013e3181bb6c09
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Lymphangioma-like Adenomatoid Tumor of the Adrenal Gland: Case Presentation and Review of the Literature

Abstract: Adenomatoid tumors (AT) are usually found in the genital tract of both sexes. They are very rarely located in extragenital sites, and are exceedingly rare in the adrenal. AT of the adrenal gland (AT-AG) are nonfunctioning, usually discovered incidentally and confused on imaging with other more common adrenal neoplasms. The overwhelming majority occur in males. Thirty-four cases have been reported so far, more often presenting grossly as solid tumors, rarely as solid with cystic areas, and 5 cases were almost e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…Berthet et al [15] mentioned three cases; however, one of the described patients was previously reported by the same authors [40]. Constantino et al [14,41] reported the same patient twice, whereas Bisceglia et al [37] described a case of lymphangioma like adenomatoid tumor and was excluded from our analysis. In five cases, we were unable to obtain the data and were also excluded from the analysis [4,6,9,18,20].…”
Section: Methodscontrasting
confidence: 48%
“…Berthet et al [15] mentioned three cases; however, one of the described patients was previously reported by the same authors [40]. Constantino et al [14,41] reported the same patient twice, whereas Bisceglia et al [37] described a case of lymphangioma like adenomatoid tumor and was excluded from our analysis. In five cases, we were unable to obtain the data and were also excluded from the analysis [4,6,9,18,20].…”
Section: Methodscontrasting
confidence: 48%
“…Our series demonstrates that the majority of OANs are also positive for calretinin (9 of 13 cases). This is not unexpected given that conventional adrenocortical neoplasms are commonly positive for this antibody [15], a finding that likely relates to the shared embryological origin of adrenocortical cells and coelomic epithelium (for which calretinin is a marker [16]), as also attested to by tumors of mesothelium, which rarely arise within the adrenal glands [17,18]. However, calretinin immunoreactivity specifically in the setting of OANs has not been previously described.…”
Section: Discussionmentioning
confidence: 61%
“…However, other sites such as intestinal mesentery, omentum, pancreas, heart, and pleura have also been documented. To the best of our knowledge <40 cases of adenomatoid tumour of adrenal gland have been reported in the English literature [120]. The adrenal gland is devoid of a mesothelial lining, and the most accepted hypothesis for an adenomatoid tumour originating in the adrenal gland is derivation from mesothelial rests.…”
Section: Introductionmentioning
confidence: 99%